Relationship between the perception of employee rotation and nurse performance during the COVID-19 pandemic - Fahrudi, Eka; Lumadi, Sih Ageng; Maria, Lilla (The Journal of Palembang Nursing Studies, 2023)
Background: COVID-19 has had an impact on nurse exposure, including in the operating room. Nurse rotation is intended to minimize exposure to COVID-19. However, problems caused by nurse rotation might interfere with nurse performance due to the rapid adaptation required. Objective: This study aims to determine the relationship between employee rotation and the performance of nurses during the COVID-19 pandemic. Methods: An analytical descriptive cross-sectional study involving 45 nurses was conducted using purposive sampling technique. Data were collected using a job rotation questionnaire and a nurse performance questionnaire. The data were analyzed using the Spearman rho test with a significance level of 95%.  Results: Out of 45 respondents, 29 (64.4%) had a moderate perception of nurse rotation, and 28 (62.2%) demonstrated good nurse performance. There was no significant relationship found between nurse rotation and nurse performance (p>0.05). Conclusions: It is recommended that nurses comply with the employee rotation policy to minimize contact with COVID-19 patients, reduce work stress, and enhance new competencies.